2016
DOI: 10.1111/1754-9485.12488
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels of paediatric computed tomography examinations performed at a dedicated Australian paediatric hospital

Abstract: Introduction: Diagnostic Reference Levels (DRL) of procedures involving ionizing radiation are important tools to optimizing radiation doses delivered to patients and in identifying cases where the levels of doses are unusually high. This is particularly important for paediatric patients undergoing computed tomography (CT) examinations as these examinations are associated with relatively high-dose. Methods: Paediatric CT studies, performed at our institution from January 2010 to March 2014, have been retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…There are many studies in the world that have provided DRLs for paediatric CT, such as Italian nationwide survey (2015) [20], Australia (2016) [21], Australia (2018) [22], France (2011) [23], France (2020) [14,15], Japan (2015) [24], Germany (2016) [25], England (2018) [26], Finland (2015) [27], the results from multicentre study in California, USA (2015) [28] and the European DRL (2018) [17]. We believe that the concept of AQD that integrates image quality with dose shall be found to be meaningful and our results shall provide reference values for future studies on AQD.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in the world that have provided DRLs for paediatric CT, such as Italian nationwide survey (2015) [20], Australia (2016) [21], Australia (2018) [22], France (2011) [23], France (2020) [14,15], Japan (2015) [24], Germany (2016) [25], England (2018) [26], Finland (2015) [27], the results from multicentre study in California, USA (2015) [28] and the European DRL (2018) [17]. We believe that the concept of AQD that integrates image quality with dose shall be found to be meaningful and our results shall provide reference values for future studies on AQD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that probability exists for a significant DLP variation between radiographers even in the setting of a dedicated paediatric hospital. 24 …”
Section: Discussionmentioning
confidence: 99%
“…A discrepancy in the comparison of CTDI vol and DLP values for a specific examination in a specific age category is likely because of a larger-than-expected pre-selected scan area for the particular study. 24 , 25 This and the fact that the CT brain values compared better than the CT chest and abdomen values could be a result of using age, rather than weight, as an input parameter for CT chest and abdomen examination in children. 10…”
Section: Discussionmentioning
confidence: 99%
“…The paediatric patient dose data analysed here are from the examinations performed at the Women's and Children's Hospital (WCH) in Adelaide. In particular, computed tomography (CT), fluoroscopy and nuclear medicine examinations are from these modality's databases. Minimum, maximum and average effective doses have been calculated for CT, fluoroscopic, general radiographic and nuclear medicine examinations in the age groups 0 to <5 years, 5 to <10 years, 10 to <15 years and 15 to <18 years.…”
Section: Methodsmentioning
confidence: 99%